The Effectiveness of Gorontalo Local Wisdom-Based Ethnomathematics in Enhancing Mathematics Understanding - Pongoliu, Yusraningsih H. (Journal La Edusci, 2025)
The present research addressed the question of how ethnomathematics-led learning can promote the learning of plane geometry in elementary students by combining the local cultural heritage elements of the Gorontalo community, namely Payango traditional house, to mathematics education. Seeking to utilize a quasi-experimental pre-test post-test design, 30 students in three elementary schools were randomly divided into experimental and control groups. The experimental group was exposed to mathematics learning in the context of the geometry of the Payango house whereas the control group was taught normally. In the statistical analysis, the experimental group reported that much better results were attained in the Comprehension of mathematics, both in terms of post-test score and standard deviation than the control group (p = 0.002). In addition to enhanced cognition, the students who encountered ethnomathematics expressed increased motivation, engagement, and relevance in the learning of mathematics as well as its owning. These results denote that ethnomathematics has more to offer to enhance performance: this mathematics is introduced as meaningful, culturally related knowledge, which contributes to conceptualisation and positive mathematical attitude. The study highlights the potential of ethnomathematics to promote educational equity, cultural affirmation, and deeper learning. It calls for its systematic integration into curricula, supported by teacher development and inclusive instructional design, and identifies the need for future longitudinal and cross-context research to further explore its transformative possibilities.